2004
DOI: 10.1038/nn1172
|View full text |Cite
|
Sign up to set email alerts
|

Cortical neurons arise in symmetric and asymmetric division zones and migrate through specific phases

Abstract: Precise patterns of cell division and migration are crucial to transform the neuroepithelium of the embryonic forebrain into the adult cerebral cortex. Using time-lapse imaging of clonal cells in rat cortex over several generations, we show here that neurons are generated in two proliferative zones by distinct patterns of division. Neurons arise directly from radial glial cells in the ventricular zone (VZ) and indirectly from intermediate progenitor cells in the subventricular zone (SVZ). Furthermore, newborn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

64
2,070
4
16

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,012 publications
(2,154 citation statements)
references
References 48 publications
64
2,070
4
16
Order By: Relevance
“…Transitions occur at mitosis but not along the cell cycle between mitoses, when bRGCs remain stable as a single morphotype. This remarkable lineage plasticity between bRGCs and IPCs, and its apparent reversibility (bRGC‐to‐IPC, and IPC‐to‐bRGC) is in sharp contrast with current observations in mouse where the sequence aRGC‐to‐IPC or aRGC‐to‐bRGC is irreversible (Betizeau et al, 2013; Noctor et al, 2004; Shitamukai et al, 2011; Wang et al, 2011). Given that these transitions are a dynamic feature, it will require using similar videomicroscopy approaches to define if they also occur in other species, and at which frequency.…”
Section: Variations On a Mouse Theme: Toward A Global Understandingcontrasting
confidence: 86%
See 1 more Smart Citation
“…Transitions occur at mitosis but not along the cell cycle between mitoses, when bRGCs remain stable as a single morphotype. This remarkable lineage plasticity between bRGCs and IPCs, and its apparent reversibility (bRGC‐to‐IPC, and IPC‐to‐bRGC) is in sharp contrast with current observations in mouse where the sequence aRGC‐to‐IPC or aRGC‐to‐bRGC is irreversible (Betizeau et al, 2013; Noctor et al, 2004; Shitamukai et al, 2011; Wang et al, 2011). Given that these transitions are a dynamic feature, it will require using similar videomicroscopy approaches to define if they also occur in other species, and at which frequency.…”
Section: Variations On a Mouse Theme: Toward A Global Understandingcontrasting
confidence: 86%
“…2). In agreement with this notion, the occurrence of direct neurogenesis in the mouse cerebral cortex is remarkably infrequent (Attardo et al, 2008; Haubensak et al, 2004; Kowalczyk et al, 2009; Noctor et al, 2004). Hence, two fundamental changes must have occurred during vertebrate evolution between reptiles/birds and mammals leading to the emergence of the neocortex: (1) abundant generation of a novel type of neurogenic progenitor cell populating and dividing at basal positions in the embryonic cortex and (2) near complete suppression of the direct neurogenic program from aRGCs (Fig.…”
Section: Dawn and Expansion Of The Neocortexmentioning
confidence: 73%
“…For this study we tested the impact of constraining the directionality of differentiation, so that precursors after each division become progressively more fate constrained. Although this is a common hypothesis concerning the nature of corticogenesis (Qian et al, 1998; Noctor et al, 2004; Tyler and Haydar, 2013), we found that an explicit inclusion of this assumption leads to a model (Fig. 9) that does not match the biological reality as well as fully unconstrained models, suggesting that bidirectional transitions between most (but not all) of the precursor types would be a fundamental property that a model of primate corticogenesis should capture.…”
Section: Discussionmentioning
confidence: 99%
“…A subpopulation of bIPs with self‐renewing capacity has been reported in the rodent (Noctor et al, 2004) and human neocortex (Hansen et al, 2010; LaMonica et al, 2013). Their abundance has been speculated to be at least partially responsible for the expansion of the neocortex in gyrencephalic species (Lui et al, 2011).…”
mentioning
confidence: 92%
“…Basal intermediate progenitors (bIPs) are multipolar cells with no known polarity cues; they express the transcription factor Tbr2, and in mouse typically undergo a terminal symmetric division, generating two neurons (Englund et al, 2005; Haubensak et al, 2004; Miyata et al, 2004; Noctor et al, 2004). A subpopulation of bIPs with self‐renewing capacity has been reported in the rodent (Noctor et al, 2004) and human neocortex (Hansen et al, 2010; LaMonica et al, 2013).…”
mentioning
confidence: 99%